INTEREST RATE SENSITIVITY OF SRI RAM TRANSPORT FINANCE LIMITED (SRTFL) TAMILNADU (INDIA) - AN EMPIRICAL ANALYSIS - Reddy, Karthik; Reddy B, Dr. Ravichandra (The journal of contemporary issues in business and government, 2022)
Interest rate risk is major risk arise from dynamic market conditions and strongly affect the net interest income economy value of the financial institutions. This impact will be higher when mismatch between assets and liabilities is wider (maturity and interest rate wise). Therefore, present study analyzed the interest sensitivity of assets and liabilities in largest deposit taking NBFCs in Tamilnadu i.e. Sri Ram Transport Finance limited. The study applied GAP Analysis technique which is popular tool to measure of interest sensitivity in different time period. The study period is six years 2015-2020. The study found that significant and wider gap between assets and liabilities in very short period (1 day to 3 months) and insignificant gap in short period (3m to one year) and long period (one year to five years). Therefore, the study found that, effect of interest rate fluctuations on NII and economic value is higher in short period and insignificant short and long period.